Insights into the pH-driven emulsifying properties and self-assembly behaviour of pea peptides - Xiaoyang Sun; Yan Chen; Xinxin Xu; Pei Wang; Jinhu Tian; Meichen Liu; Xiufeng Zhang; Xiaoqing Yuan; Fusheng Chen; Lifen Zhang (Food Research International, 2026)

Metal-node coupling of triboelectricity in conductive metal–organic frameworks for contact-electro-catalytic H2O2 generation - Meichen Li; Shuqi Zhou; Yinben Guo; Xueshuang Xiao; Qiqing Xi; Ximing Wang; Xin Han; Qiang Yang (Chemical Engineering Journal, 2026)

Decoding the survival strategy of Parachlorella sp. MP1: Genomic basis and physiological adaptations to acidity and heavy metals in acid mine drainage - Meichen Wang; Lu Zhang; Zhengbo Yue; Zijie Yu; Rui Deng; Jin Wang (Bioresource Technology, 2026)

Hyperspectral response and quantitative monitoring of soil organic carbon on the Loess Plateau - Sha Yang; Zhigang Wang; Chenzhi Zheng; Yuchao Yang; Jiancheng Zhang; Xingxing Qiao; William Rickard; Yu Zhao; Meichen Feng; Longmei Gao; Wude Yang; Chao Wang (Computers and Electronics in Agriculture, 2026)

A GDD-constrained allometric framework for UAV-based estimation of winter wheat aboveground biomass - Xinglong Duan; Bokun Hao; Zhigang Wang; Yidan Ding; Yufei Wang; Qianyu Wang; Zhenwei Yang; Chenbo Yang; Yu Zhao; Chao Wang; Lujie Xiao; Meijun Zhang; et al. (Computers and Electronics in Agriculture, 2026)

Corrigendum to “Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics” [Food Chem. 513 (2026) 149020] - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

Changes in ginseng wine flavor characteristics during fermentation with Saccharomyces cerevisiae - Shen Yao; Yang Li; Xianwei Zeng; Yuan Cui; Zhaolian Li; Meichen Liu; Daqing Zhao; Shiting Yu; Siming Wang (Food Chemistry, 2026)

Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

Rapid fractionation of moso bamboo using ternary deep eutectic solvent for integrated enzymatic hydrolysis and in situ treatment liquid gelation - Jiaying Li; Chengcheng Yuan; Meichen Zhang; Yingchao Wang; Feng Xu; Fengshan Zhang; Zongwei Guo; Hao Ma; Xingxiang Ji (Chemical Engineering Journal, 2026)

Dual-phase transcriptional regulation enables efficient denitrification by Stutzerimonas degradans BP under saline stress - Yanjie Niu; Qiwen Bie; Jin Wang; Zhengbo Yue; Meichen Wang; Yifan Jiang; Shu Wang (Journal of Environmental Chemical Engineering, 2026)

Decoupling of arbuscular mycorrhizal fungi and soil organic carbon under nitrogen addition in terrestrial ecosystems: a meta-analysis - Andi Li; Jing Chen; Senhao Wang; Guangcan Yu; Meichen Xu; Anchi Wu; Jinhua Mao; Wei Zhang; Zhanfeng Liu; Juxiu Liu; Jiangming Mo; Mianhai Zheng (Frontiers of Earth Science, 2026)

Hyperspectral estimation on the photosynthetic phenotype of winter wheat under drought stress using machine learning algorithms - Yanxia Chen; Xiaobin Yan; Tingyue Huo; Yuchao Yang; Bei Tie; Chenhao Qin; Meichen Feng; Xingxing Qiao; Xiaokai Chen; Guangxin Li; Chao Wang; Wude Yang (Precision Agriculture, 2026)

Predicting the toxicity of organic chemicals to Tetrahymena pyriformis based on machine learning and interpretable models - Meichen Sun; Handong Yu; Caige Lu; Yue Wang; Minghui He; Dongmei Zheng; Xiaotian Xu; Limin Su; Yuanhui Zhao (Process Safety and Environmental Protection, 2026)

Microalgae-bacteria interactions in acidic mining pit lakes: Community assembly and environmental drivers - Meichen Wang; Jin Wang; Xin Pan; Zijie Yu; Ziyi Li; Rui Deng; Zhengbo Yue (Process Safety and Environmental Protection, 2026)

Regulating mineral ions to enhance uranium phytoremediation by Macleaya cordata under synergistic effects of oxalic acid and Fusarium sp. A-2 - Meichen Li; Huang Yu; Tao Lang; Qinwen Deng; Weichao Zhao; Hui Zhang; Yuan Xue; Yongdong Wang; Dexin Ding; Nan Hu (Journal of Environmental Radioactivity, 2026)

Synergistic enhancement of phytoremediation efficiency and mechanisms of uranium-contaminated soil by oxalic acid and endophytic fungus Fusariumsp. A-2 withMacleaya cordata - Kongjun Zhu; Zhaolan Yang; Meichen Li; Qinwen Deng; Fangfang Xiao; Yongdong Wang; Dexin Ding; Huang Yu; Nan Hu (Journal of Environmental Radioactivity, 2026)

Modelling green space accessibility and equity in mountainous cities: a case study of Chongqing - Yuhan Wang; Keyu Luo; Zhenyu Wang; Meichen Fu (Environment, Development and Sustainability, 2025)

Integrating leaf-scaled spectra and machine learning for rapid estimation of photosynthetic phenotypes across soybean genotypes - Chao Wang; Xiaobin Yan; Yan Bai; Jiaxue Zhang; Xinhui Guo; Xiaomei Zhang; Meichen Feng; William Rickard; Yu Zhao; Fangzhou Li; Chenbo Yang; Xiaokai Chen; et al. (Computers and Electronics in Agriculture, 2025)

Human activities challenge carbon storage in the Yangtze River Delta, China - Meichen Jiang; Xin Wang; Pengcheng Liu; Nana Zhang (Journal of Environmental Management, 2025)

Small lakes, big improvements: a multi-decadal assessment of policy and climate impacts on chlorophyll-a in China - Sijia Li; Hong Yang; Ge Liu; Dehua Mao; Zongming Wang; Haiqing Liao; Lele Zhang; Haoyun Zhou; Meichen Ji; Kaishan Song (Science Bulletin, 2025)

Monitoring the growth status of winter wheat by using the machine learning algorithm and the fusion of spectral and texture features derived from the UAV remote sensing - YiMing Su; XiaoBin Yan; Hao Li; ZiHao Liang; ShuangMei Zhao; Ping Chen; Zhen Zhang; XingXing Qiao; Yu Zhao; MeiChen Feng; Fahad Shafiq; XiaoYan Song; et al. (Computers and Electronics in Agriculture, 2025)

SiO2 NP promotes allergic gastritis induced by degranulation of mouse MC9 cell through AQP4-mediated impairment of SIRT3-TFAM deacetylation and mitochondrial autophagy - Yutian Lei; Xiaodan Wang; Hao Wu; Meichen Gao; Tong Xu; Hongjin Lin (Journal of Hazardous Materials, 2025)

Under the combined application of selenium and sulfur, sulfur does not interfere with selenite uptake in Tartary buckwheat - Shangqun Ji; Panfeng Liu; Shuangmei Zhao; Minghui Dai; Wenbo Han; Zhen Zhang; Chao Wang; Fahad Shafiq; Xingxing Qiao; Lujie Xiao; Meichen Feng; Meijun Zhang; et al. (Food Chemistry, 2025)

Elucidating the occurrence patterns of Alternaria toxin tenuazonic acid in individual tomatoes through MALDI-MSI and LC-MS/MS - Fan Sun; Yingying Fan; Yingying Dai; Muhai Tang; Jiangtao Du; Anqi Xu; Meichen Liu; Qianqian Chu; Dianzhen Yu; Ye Tian; Xiyan Sun; Weiheng Ren; et al. (Food Chemistry, 2025)

Complexes of Dendrobium officinale anthocyanins and polysaccharides: Structural characteristics, stability, antioxidant properties, and bioavailability - Bowen Sui; Yanling Sun; Jingzhi Wang; Yuan Cui; Haibo Xu; Daqing Zhao; Meichen Liu; Zhengqi Dong; Siming Wang; Shichao Liu (Food Bioscience, 2025)

Per- and polyfluoroalkyl substances (PFAS) toxicity and mitigation of adipogenic dysregulation in 3T3-L1 preadipocytes - Qinfu Wang; Soonkyu Chung; Meichen Wang (Food and Chemical Toxicology, 2025)

A galacturonan from sea buckthorn (Hippophae rhamnoides L.) berry modulates dyslipidemia by promoting hepatic lipolysis and mitochondrial oxidation - Yunpeng Sun; Weifeng Ni; Dongyi Wang; Jixiang Ren; Daqing Zhao; Shiting Yu; Shichao Liu; Shaojie Zhang; Siming Wang; Weinan Wang; Meichen Liu (Carbohydrate Polymers, 2025)

Plant morphological and physiological traits are stable in a nitrogen-saturated tropical forest after 18-year nitrogen additions - Guangcan Yu; Jing Chen; Andi Li; Senhao Wang; Liang Song; Xianmeng Shi; Junhua Yan; Meichen Xu; Yuewei Xue; Xiankai Lu; Wei Zhang; Juan Huang; et al. (Plant and Soil, 2025)

Mitigation of PFAS toxicity through sorbent treatment in Sprague-Dawley rats during prenatal and postnatal exposure - Meichen Wang; Johnson O. Oladele; Kelly J. Rivenbark; Timothy D. Phillips (Toxicology, 2025)

Hyperspectral assessment of bacterial blight disease in red kidney beans by feature selection and machine learning algorithms - Xingxing Qiao; Jiachen Wang; Binghan Jing; Xin Zhang; Yaoxuan Jia; Kunming Huang; Wude Yang; Meichen Feng; Zhen Zhang; Yu Zhao; Fahad Shafiq; Lujie Xiao; et al. (Precision Agriculture, 2025)

Functional analysis of Mu-class glutathione S-transferase HdGSTm1 from Haemaphysalis doenitzi with a focus on the roles in the tick blood sucking - Xiaolong Yang; Kuang Wang; Meichen Zhao; Feidi Guo; Runying Wang; Jianing Liu; Zhihua Gao (Experimental and Applied Acarology, 2025)

Comparative analysis of the effects of different dimensionality reduction algorithms on hyperspectral estimation of total nitrogen content in wheat soils - Juan Bai; Shiyou Zhu; Yingchao Hao; Xinzhe Li; Chenbo Yang; Chao Wang; Xingxing Qiao; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Sha Yang; et al. (European Journal of Agronomy, 2025)

A UAV-based hybrid approach for improving aboveground dry biomass estimation of winter wheat - Yu Zhao; Haikuan Feng; Shaoyu Han; Chao Wang; Meichen Feng; Lujie Xiao; Zhenhai Li; Wude Yang; Guijun Yang (European Journal of Agronomy, 2025)

Magnetic properties of agricultural soils and their relationships with environmental factors in Jinghong, Yunnan, China - Meichen Wang; Haixia Li; Shiyu Li; Yudong Chen; Gangqiang Li (Earth Science Informatics, 2025)

Seasonal variation drives species coexistence and community succession in microbial communities of stratified acidic pit lakes - Meichen Wang; Xin Pan; Zhengbo Yue; Rui Deng; Ziyi Li; Jin Wang (Journal of Environmental Management, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Ordered crystal growth of 2D Ruddlesden–Popper perovskites via synergistic fluorination and chlorination for efficient and stable 2D/3D heterostructure perovskite solar cells - Shitong Du; Wenbin Yang; Wending Hao; Tao Liu; Meichen Hou; Ning Wang (Chemical Engineering Journal, 2025)

Adsorption of Per- and Polyfluoroalkyl Substances by Edible Nutraceutical-Amended Montmorillonite Clays: In Vitro, In Vivo and In Silico Enterosorption Strategies - Johnson O. Oladele; Xenophon Xenophontos; Meichen Wang; Phanourios Tamamis; Timothy D. Phillips (Water, Air, & Soil Pollution, 2025)
Exposure of animals and humans to PFAS through contaminated water and foods pose significant threats to public health. To tackle this challenge, this study aimed to develop edible clays that might enhance the binding, detoxification, and elimination of PFAS in the gastrointestinal tract. Montmorillonite clays (CM) were amended with caffeine (CMCAF), curcumin (CMCUR), and riboflavin (CMRIB), and the binding efficacy for a mixture of four PFAS (PFOS, GenX, PFOA and PFBS) was determined. In vitro studies were used to explore adsorption isotherms while computational simulations investigate PFAS mixture, delineate the contribution of each PFAS molecule to clays and determine if amended clays can contribute to enhanced binding of different PFAS in the mixture. In vivo models ( Lemna minor and Hydra vulgaris ) were used to validate in vitro and in silico studies and establish the safety and effectiveness of these amended clays. The resulting Q max and K d values along with the curved shape of the Langmuir plot indicated saturable binding of GenX, PFOA and PFOS to active surfaces of CM and the amended clays. All three clays demonstrated a slightly higher binding capacity for GenX than the parent clay. Furthermore, the simulations elucidated the binding contribution of each PFAS molecule to parent and amended clays as well as predicting how amended clays can contribute to mechanisms of binding of different PFAS in the mixture. The proof-of-concept for the efficacy of the clays was established in Caenorhabditis elegans, Lemna minor and Hydra vulgaris , where the clays (at 1% w/v inclusion) protected against toxicities of the four PFAS controls. This protection could be attributed to PFAS binding to the amended clays and the biological activities of these nutraceuticals (caffeine, riboflavin, and curcumin) including antioxidative, anti-inflammatory and modulatory activities which mitigate the oxidative stress and inflammatory effects of PFAS. These edible toxin binders may be delivered in mixtures as additives in flavored drinking water and food to decrease PFAS exposure.

Chemical synergic lead fixation toward efficient and sustainable perovskite solar cells - Wenbin Yang; Shitong Du; Tao Liu; Meichen Hou; Wending Hao; Ning Wang (Chemical Engineering Journal, 2025)

Mechanism of decolorization and degradation of direct brown D3G by a halo-thermophilic consortium - Wenying Wang; Zuotao Zhang; Meichen Sun; Chenlai Li; Mengdi Yan; Chongyang Wang (Extremophiles, 2025)

A new feature selection algorithm combining genetic algorithm, exponential decay function, and machine learning to realize hyperspectral estimation of winter wheat leaf area index - Chenbo Yang; Juan Bai; Hui Sun; Rutian Bi; Lifang Song; Amjad Muhammad; Chao Wang; Yu Zhao; Wude Yang; Lujie Xiao; Meijun Zhang; Xiaoyan Song; et al. (Computers and Electronics in Agriculture, 2025)

Evaluating the potential of airborne hyperspectral imagery in monitoring common beans with common bacterial blight at different infection stages - Binghan Jing; Jiachen Wang; Xin Zhang; Xiaoxiang Hou; Kunming Huang; Qianyu Wang; Yiwei Wang; Yaoxuan Jia; Meichen Feng; Wude Yang; Chao Wang (Biosystems Engineering, 2025)

Molecular disruptions in microalgae caused by Acidithiobacillus ferrooxidans: Photosynthesis, oxidative stress, and energy metabolism in acid mine drainage - Meichen Wang; Zhengbo Yue; Rui Deng; Zhixiang She; Lu Zhang; Fan Yang; Jin Wang (Water Research, 2025)

Analysis of sediment re-formation factors after ginseng beverage clarification based on XGBoost machine learning algorithm - Jiabao Feng; Yuan Cui; Chunyan Jiang; Xueyuan Bai; Daqing Zhao; Meichen Liu; Zhengqi Dong; Shiting Yu; Siming Wang (Food Chemistry, 2025)

Resveratrol alleviates Mono-2-ethylhexyl phthalate-induced mitophagy, ferroptosis, and immunological dysfunction in grass carp hepatocytes by regulating the Nrf2 pathway - Xiaodan Wang; Meichen Gao; Xiunan Lu; Yutian Lei; Jiatong Sun; Mengyao Ren; Tong Xu; Hongjin Lin (Journal of Environmental Management, 2024)

Photolysis of p-phenylenediamine rubber antioxidants in aqueous environment: Kinetics, pathways and their photo-induced toxicity - Chen Wang; Meichen Sun; Minghui He; Siyu Zhao; Meinuo Lv; Xiaotian Xu; Chunbei Ye; Linjing Li; Limin Su; Yuanhui Zhao (Journal of Hazardous Materials, 2024)

Analyzing the variation of greenhouse gas emissions from typical municipal wastewater treatment plants in Beijing during 2007–2021 - Meichen Ji; Haiqing Liao; Zhibo Lu; Lianhua Mao; Xingxuan Zhou; Fang Yang; Dongxia Feng; Qianqian Wang (Environmental Pollution, 2024)

Quercetin antagonizes apoptosis, autophagy and immune dysfunction induced by di(2-ethylhexyl) phthalate via ROS/ASK1/JNK pathway - Jiatong Sun; Xiaodan Wang; Tong Xu; Mengyao Ren; Meichen Gao; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Changes in the magnetic properties of a tropical red soil following the conversion of forest into agricultural land - Meichen Wang; Fengrui Li; Haixia Li; Xiaoling Zhang; Shiyu Li; Gangqiang Li; Yudong Chen; Yang Wang; Jingyuan Hu; Junmin Ye (Journal of Applied Geophysics, 2024)

Distribution characterization of MPs and DOM in ice-covered season in a saline-alkaline Lake in Daihai with an innovative analysis using 2DCOS and structural equation modelling - Ting Pan; Fang Yang; Haiqing Liao; Zhiming Han; Meichen Ji; Qianqian Wang; Hao Yang; Matti Leppäranta (Journal of Hydrology, 2024)

Combined exposure of emamectin benzoate and microplastics induces tight junction disorder, immune disorder and inflammation in carp midgut via lysosome/ROS/ferroptosis pathway - Xu Shi; Tong Xu; Meichen Gao; Yanju Bi; Jiaqi Wang; Yilin Yin; Shiwen Xu (Water Research, 2024)

Green pretreatment of lignocellulosic biomasses via deep eutectic solvents - Yingxia Guo; Jiaxin Zhang; Chuya Wang; Meichen Liu; Jiansong You; Lei Yin; Meiyun Shi (Sustainable Chemistry and Pharmacy, 2024)

Characteristics of the presence and migration patterns of DOM between ice and water in the cold and arid Daihai Lake - Ting Pan; Yimeng Zhang; Fang Yang; Haiqing Liao; Weiying Feng; Fuhong Sun; Weilong Jiang; Qianqian Wang; Meichen Ji; Chenglei Yang; Matti Leppäranta (Science of The Total Environment, 2024)

Using L. minor and C. elegans to assess the ecotoxicity of real-life contaminated soil samples and their remediation by clay- and carbon-based sorbents - Kelly J. Rivenbark; Leanne S. Fawkes; Hasan Nikkhah; Meichen Wang; Garett T. Sansom; Burcu Beykal; Terry L. Wade; Timothy D. Phillips (Environmental Pollution, 2024)

In vitro and in vivo remediation of per- and polyfluoroalkyl substances by processed and amended clays and activated carbon in soil - Meichen Wang; Kelly J. Rivenbark; Hasan Nikkhah; Burcu Beykal; Timothy D. Phillips (Applied Soil Ecology, 2024)

Combined use of spectral resampling and machine learning algorithms to estimate soybean leaf chlorophyll - Chunrui Gao; Hao Li; Jiachen Wang; Xin Zhang; Kunming Huang; Xiaoyan Song; Wude Yang; Meichen Feng; Lujie Xiao; Yu Zhao; Fahad Shafiq; Chao Wang; et al. (Computers and Electronics in Agriculture, 2024)

Toxicity of representative organophosphate, organochlorine, phenylurea, dinitroaniline, carbamate, and viologen pesticides to the growth and survival of H. vulgaris, L. minor, and C. elegans - Kelly J. Rivenbark; Hasan Nikkhah; Meichen Wang; Burcu Beykal; Timothy D. Phillips (Environmental Science and Pollution Research, 2024)

Efficient prediction of SOC and aggregate OC components by continuous wavelet transform spectra under different feature selection methods - Sha Yang; Zhigang Wang; Caiyu Ji; Yingchao Hao; Zihao Liang; Xiaobin Yan; Xingxing Qiao; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Guangxin Li; et al. (Computers and Electronics in Agriculture, 2024)

Adsorption and removal of polystyrene nanoplastics from water by green-engineered clays - Meichen Wang; Kendall Lilly; Leisha M.A. Martin; Wei Xu; Phanourios Tamamis; Timothy D. Phillips (Water Research, 2024)

Green-engineered clay- and carbon-based composite materials for the adsorption of benzene from air - Kelly J. Rivenbark; Kendall Lilly; Meichen Wang; Phanourios Tamamis; Timothy D. Phillips (Journal of Environmental Chemical Engineering, 2024)

Kinetics of glyphosate and aminomethylphosphonic acid sorption onto montmorillonite clays in soil and their translocation to genetically modified corn - Meichen Wang; Kelly J Rivenbark; Timothy D Phillips (Journal of Environmental Sciences, 2024)

Sodium selenite (Na2SeO3) attenuates T-2 toxin-induced iron death in LMH cells through the ROS/PI3K/AKT/Nrf2 pathway - Xinrui Deng; Tingting Yu; Meichen Gao; Jiaqi Wang; Wenying Sun; Shiwen Xu (Food and Chemical Toxicology, 2023)

Efficient antibiotic wastewater treatment via interfacial water evaporation based soot-coated conjugated microporous polymer hollow microspheres - Wenwen Luo; Meichen Liu; Rui Jiao; Yunjia Wang; Jiyan Li; Zhaoqi Zhu; Weidong Liang; Hanxue Sun; An Li (Chemical Engineering Journal, 2023)

A new flavonoid glycoside from Toxicodendron vernicifluum (Stokes) F.A. Barkley - Chengye Zhao; Meichen Li; Yuqian Yang; Minni Qin; Ruojia Wang; Qing Zhu; Guangtong Chen; Andong Wang (Natural Product Research, 2023)

Optimization of SbBix nanoparticles embedded in ultra-thin carbon networks for enhanced sodium/potassium storage - Qingxin Lin; Jian Qin; Yanyan Cao; Xiaokang Li; Yan Hong; Meichen Jin; Jinjuan Dong; Wei Xiao; Wenbin Li; Jingjing Wang; Xifei Li (Chemical Engineering Journal, 2023)

Association between ADAMTS14_rs4747096 gene polymorphism and bone mineral density of Chinese Han population residing in fluorine exposed areas in ShanXi Province, China - Ming Qin; Yue Gao; Meichen Zhang; Junhua Wu; Yang Liu; Yuting Jiang; Xiaodi Zhang; Xin Wang; Yanmei Yang; Yanhui Gao (Environmental Science and Pollution Research, 2023)

Evodiamine alleviates DEHP-induced hepatocyte pyroptosis, necroptosis and immunosuppression in grass carp through ROS-regulated TLR4 / MyD88 / NF-κB pathway - Yutian Lei; Tong Xu; Wenying Sun; Xiaodan Wang; Meichen Gao; Hongjin Lin (Fish & Shellfish Immunology, 2023)

Molecular insights into the impacts of acid mine drainage on dissolved organic matter dynamics in pit lakes - Zhixiang She; Jin Wang; Chen He; Zhengfeng Jiang; Xin Pan; Meichen Wang; Ding Ma; Quan Shi; Zhengbo Yue (Science of The Total Environment, 2023)

Multivariate prediction of soil aggregate-associated organic carbon by simulating satellite sensor bands - ChunRui Gao; XiaoBin Yan; XingXing Qiao; KunXi Wei; XiaoMei Zhang; Sha Yang; Chao Wang; WuDe Yang; MeiChen Feng; LuJie Xiao; MeiJun Zhang; Zhou Zhang; et al. (Computers and Electronics in Agriculture, 2023)

Evaluation of data pre-processing and regression models for precise estimation of soil organic carbon using Vis–NIR spectroscopy - Yaxin Wang; Sha Yang; Xiaobin Yan; Chenbo Yang; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Fahad Shafiq; Hui Sun; Guangxin Li; Wude Yang; et al. (Journal of Soils and Sediments, 2023)

Spillover-feedback effects of employment, energy, economy and environment (4E) between domestic-owned and foreign-invested enterprises: Taking China as an example - Junjun Hou; Youfu Yue; Qian Wang; Jiabai Ye; Meichen Zhang (Journal of Cleaner Production, 2023)

Adsorption and detoxification of glyphosate and aminomethylphosphonic acid by montmorillonite clays - Meichen Wang; Kelly J. Rivenbark; Timothy D. Phillips (Environmental Science and Pollution Research, 2022)

Hyperspectral monitoring of soil urease activity under different water regulation - Chenbo Yang; Meichen Feng; Lifang Song; Binghan Jing; Yongkai Xie; Chao Wang; Mingxing Qin; Wude Yang; Lujie Xiao; Jingjing Sun; Meijun Zhang; Xiaoyan Song; et al. (Plant and Soil, 2022)

Isolation of a new monoterpenoid glycoside from Anhua dark tea based on an NMR-guided method and its cytotoxic activity against MDA-MB-231 and SH-SY5Y cell lines - Yunqiang Zhang; Jianyu Liu; Miao Chen; Yanhua Fan; Meichen Li; Andong Wang; Gaigai Liu; Yongnan Xu; Xuhong Ren; Yan Xiao (Natural Product Research, 2022)

A novel defensin-like peptide contributing to antimicrobial and antioxidant capacity of the tick Dermacentor silvarum (Acari: Ixodidae) - Fengjiao Li; Zhihua Gao; Kuang Wang; Yinan Zhao; Hui Wang; Meichen Zhao; Yawen Zhao; Lingqian Bai; Zhijun Yu; Xiaolong Yang (Experimental and Applied Acarology, 2021)

Tight sorption of arsenic, cadmium, mercury, and lead by edible activated carbon and acid-processed montmorillonite clay - Meichen Wang; Gopal Bera; Kusumica Mitra; Terry L. Wade; Anthony H. Knap; Timothy D. Phillips (Environmental Science and Pollution Research, 2021)

Risks Assessment Associated with Different Sources of Metals in Abandoned Soil of Zhuxianzhuang Coal Mine, Huaibei Coalfield (Anhui, China) - Hongxia Fang; Herong Gui; Jun Li; Hao Yu; Meichen Wang; Yaqi Jiang; Chunlei Wang; Chen Chen; Yaru Zhang; Yiheng Huang (Bulletin of Environmental Contamination and Toxicology, 2021)

Comparative transcriptomic and metabolomic analyses of carotenoid biosynthesis reveal the basis of white petal color in Brassica napus - Ledong Jia; Junsheng Wang; Rui Wang; Mouzheng Duan; Cailin Qiao; Xue Chen; Guoqiang Ma; Xintong Zhou; Meichen Zhu; Fuyu Jing; Shengsen Zhang; Cunmin Qu; et al. (Planta, 2021)
Main conclusion The molecular mechanism underlying white petal color in Brassica napus was revealed by transcriptomic and metabolomic analyses. Abstract Rapeseed ( Brassica napus L.) is one of the most important oilseed crops worldwide, but the mechanisms underlying flower color in this crop are known less. Here, we performed metabolomic and transcriptomic analyses of the yellow-flowered rapeseed cultivar ‘Zhongshuang 11’ (ZS11) and the white-flowered inbred line ‘White Petal’ (WP). The total carotenoid contents were 1.778-fold and 1.969-fold higher in ZS11 vs. WP petals at stages S2 and S4, respectively. Our findings suggest that white petal color in WP flowers is primarily due to decreased lutein and zeaxanthin contents. Transcriptome analysis revealed 10,116 differentially expressed genes with a fourfold or greater change in expression ( P -value less than 0.001) in WP vs. ZS11 petals, including 1,209 genes that were differentially expressed at four different stages and 20 genes in the carotenoid metabolism pathway. BnNCED4b , encoding a protein involved in carotenoid degradation, was expressed at abnormally high levels in WP petals, suggesting it might play a key role in white petal formation. The results of qRT-PCR were consistent with the transcriptome data. The results of this study provide important insights into the molecular mechanisms of the carotenoid metabolic pathway in rapeseed petals, and the candidate genes identified in this study provide a resource for the creation of new B. napus germplasms with different petal colors.

Edible clay inclusion in the diet of oysters can reduce tissue residues of polychlorinated biphenyls - Meichen Wang; Timothy D. Phillips (Toxicology and Environmental Health Sciences, 2020)

An integrated system for rapid assessment of ecological quality based on remote sensing data - Qian Ding; Li Wang; Meichen Fu; Ni Huang (Environmental Science and Pollution Research, 2020)

A high capacity bentonite clay for the sorption of aflatoxins - Meichen Wang; Sara E. Hearon; Timothy D. Phillips (Food Additives & Contaminants: Part A, 2020)

Spatiotemporal variation and influencing factors of vegetation cover in the ecologically fragile areas of China from 2000 to 2015: a case study in Shaanxi Province - Dingrao Feng; Jinman Wang; Meichen Fu; Guangchao Liu; Min Zhang; Rongbin Tang (Environmental Science and Pollution Research, 2019)

Identification of novel reference genes using sika deer antler transcriptome expression data and their validation for quantitative gene expression analysis - Meichen Liu; Baojin Yao; Hui Zhang; Huanyu Guo; Dongyang Hu; Qun Wang; Yu Zhao (Genes & Genomics, 2014)

Assessment of landscape patterns affecting land surface temperature in different biophysical gradients in Shenzhen, China - Miaomiao Xie; Yanglin Wang; Qing Chang; Meichen Fu; Minting Ye (Urban Ecosystems, 2013)

Pattern dynamics of thermal-environment effect during urbanization: A case study in Shenzhen City, China - Miaomiao Xie; Yanglin Wang; Meichen Fu; Dingxuan Zhang (Chinese Geographical Science, 2013)

De novo characterization of the antler tip of Chinese Sika deer transcriptome and analysis of gene expression related to rapid growth - Baojin Yao; Yu Zhao; Qun Wang; Mei Zhang; Meichen Liu; Hailong Liu; Juan Li (Molecular and Cellular Biochemistry, 2012)